A New Navigational Tool for Pedicle Screw Placement in Patients With Severe Scoliosis: A Pilot Study to Prove Feasibility, Accuracy, and Identify Operative Challenges. Issue 4 (May 2017) - Putzier, Michael; Strube, Patrick; Cecchinato, Riccardo; Lamartina, Claudio; Hoff, Eike K.
Abstract : Study Design: Pilot study. Objective: To develop and validate the feasibility and accuracy of a newly designed navigational spinal instrument guiding tool for patient-matched thoracic and lumbar pedicle screw placement in patients with severe scoliosis, and to identify intraoperative challenges that may be relevant. Summary of Background Data: Pedicle screw placement is challenging in severely rotated scoliotic spine with small diameters and asymmetrical shape of the pedicles and vertebrae. Patient-specific drill/positioning guides with preplanned trajectory have been developed as a promising solution in spinal surgery for precise screw insertion. Methods: In 4 patients with severe scoliosis, navigational templates and models of all vertebrae to be instrumented were manufactured using a computed tomography (CT)-based 3-dimensional model of the thoracic and lumbar spine. The guides were designed differently for thoracic and lumbar segments according to the individual anatomy to achieve an optimal coupling to the surface of the patient's spine, to maximize the stability of the device itself, and to increase user friendliness for the complete screw positioning process. Intraoperative challenges and opportunities for device and process improvements regarding the handling of the guides during the surgery were recorded. Postoperatively, the intrapedicular screw positions were evaluated versus the preoperative plan and evaluated for cortical violation based on CT scans. Results: A total of 76 pedicle screws were implanted (56 thoracic, 20 lumbar). Two screws (2.6%) were assessed to be misplaced intraoperatively and repositioned. Eighty-four percent of the pedicle screws were completely intrapedicular, 96.1% within <2 mm cortical breech. CT scans did not demonstrate medial pedicle violation, or misplaced screw contact to neurovascular structures. No screw-related clinical complaints were reported postoperatively. Conclusions: The new custom-made positioning guide is a feasible navigational tool that permits a safe and accurate implantation of pedicle screws in patients with severe scoliosis.